Extracting interface correlations from the pair distribution function of composite materials. Issue 31 (30th July 2021) - Geddes, Harry S.; Hutchinson, Henry D.; Ha, Alex R.; Funnell, Nicholas P.; Goodwin, Andrew L.
Abstract : Using a non-negative matrix factorisation (NMF) approach, we show how the pair distribution function (PDF) of complex mixtures can be deconvolved into the contributions from the individual phase components and also the interface between phases. Abstract : Using a non-negative matrix factorisation (NMF) approach, we show how the pair distribution function (PDF) of complex mixtures can be deconvolved into the contributions from the individual phase components and also the interface between phases. Our focus is on the model system Fe∥Fe3 O4 . We establish proof-of-concept using idealised PDF data generated from established theory-driven models of the Fe∥Fe3 O4 interface. Using X-ray total scattering measurements for corroded Fe samples, and employing our newly-developed NMF analysis, we extract the experimental interface PDF ('iPDF') for this same system. We find excellent agreement between theory and experiment. The implications of our results in the broader context of interface characterisation for complex functional materials are discussed.